Clinical characteristics and prognosis of adult orbital cellulitis in a tertiary general hospital - Yu-Kuang Chen; Hung-Pin Tu; I-Hsien Chen (Scientific Reports)
Abstract Adult orbital cellulitis (OC) is a rare ophthalmic condition. This study aimed to identify risk factors influencing the prognosis of adult OC by evaluating the clinical characteristics and prognosis in an Asian population in southern Taiwan. In this retrospective study, OC patients were categorized based on the underlying causes of their condition: (1) preseptal cellulitis, (2) rhinosinusitis, (3) endophthalmitis, and (4) ocular implant-related infections. Prognosis was determined by changes in logarithms of the minimum resolution angle scored by the best-corrected visual acuity (LogMAR BCVA) and the hospitalization duration. Improved LogMAR BCVA and shorter hospitalization days were observed in patients with OC from preseptal cellulitis (+ 0.25, 6.2 days) and rhinosinusitis (+ 0.27, 9.3 days) compared to endophthalmitis (− 0.38, 19.8 days). Decreased LogMAR BCVA and longer hospitalization days were seen in patients with Pseudomonas aeruginosa (− 0.21, 17.25 days), while those with Staphylococcus epidermidis (0.12, 10.7 days) and methicillin-resistant Staphylococcus aureus (MRSA, 0.34, 5.5 days) had better outcomes. Besides, hypertension (− 0.27) and heart disease (-0.57), negatively affected LogMAR BCVA. OC patients from preseptal cellulitis and rhinosinusitis, or with Staphylococcus epidermidis, and MRSA generally had good outcomes. Patients with OC derived from endophthalmitis, cultured with Pseudomonas aeruginosa, or with systemic conditions were at risk for poor visual prognosis. These findings provide useful information when evaluating treatment options for OC patients. Adult orbital cellulitis (OC) is a relatively rare ophthalmic condition encountered in general clinics and emergency departments. Relative knowledge and comprehensive studies of OC remain limited. However, OC can sometimes lead to significant visual impairment, and currently, studies focusing on data from Asia remains relatively limited. We aimed to identify the risk factors associated with unfavorable outcomes and quantify their influence by evaluating the clinical characteristics and prognosis of OC in an Asian population in southern Taiwan.